Heteronuclear bimetallic fuel cell oxygen reduction catalyst and preparation method and application thereof
By doping metals in the s-region and p-region in the Fe-N-C catalyst, and using the MOF support to achieve precise doping, a Fe-based bimetallic-nitrogen-carbon catalyst with high intrinsic activity and high stability was prepared, which solved the problem of uneven distribution of active sites of existing catalysts and the degradation of metal ions in the oxygen reduction reaction.
Patent Information
- Application Number
- CN202510025294.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-01-08
AI Technical Summary
In the oxygen reduction reaction, the existing Fe-N-C catalysts have problems such as uneven distribution of electrons at active sites and the degradation of activity due to metal ions dissolution, and it is difficult to accurately construct a high-content heteronuclear metal atom pair.
By selecting metals such as Li, Na, Al doped in the s- and p-regions, using metal organic frames (MOFs) as support, introducing iron and metal sources, and achieving precise doping through strong adsorption between ions and MOFs, the Fe-based bimetallic-nitrogen-carbon catalyst is prepared.
Accurate control of the electronic structure and geometric structure of Fe-based catalysts is achieved, catalytic activity and stability are improved, and the problems of random combinations of bimetallic catalysts in the prior art are overcome.
Smart Images

Figure CN119852430A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of catalyst technology, and in particular to a heteronuclear bimetallic fuel cell oxygen reduction catalyst and a preparation method and application thereof. Background Art
[0002] Proton exchange membrane fuel cells (PEMFCs) are considered to be the most promising renewable energy conversion devices due to their low operating temperature, fast startup, high energy conversion rate, and cleanliness. However, their cathode oxygen reduction reaction (ORR) is slow and requires a large amount of platinum-based catalysts. The scarcity of catalyst resources and poor durability have seriously hindered the commercial development of PEMFCs. Therefore, non-precious metal ORR catalysts with low cost, high activity, and high stability have been widely explored and applied.
[0003] Atomically dispersed Fe-NC catalysts have made some progress in terms of activity, but there are still some challenges in practical application. The Fe-N4 / C site has a clear symmetrical electron distribution, which hinders the adsorption and activation of O2 at its site, thereby affecting the intrinsic activity of the catalyst in the ORR process. In addition, the large amount of metal ions dissolved in the Fe-NC catalyst will lead to a decrease in the density of active sites, resulting in a sharp drop in catalytic activity. Compared with traditional atomically dispersed Fe-NC catalysts, Fe-based bimetallic-nitrogen-carbon catalysts have unique advantages. First, they can optimize the adsorption and desorption rate of oxygen-containing intermediates at the active site by regulating the electronic and coordination structure of the Fe-N4 / C site, thereby further improving the electrocatalytic activity. Secondly, the introduction of the second metal atom will regulate the Fe-N bond strength, so that the Fe-based bimetallic-nitrogen-carbon catalyst has better thermodynamic stability. In the periodic table, metal atoms in different regions (s region, p region, d region, f region) have different valence electron structures, which will have different effects on the electronic distribution and geometric structure of the Fe atom in the active center, and the ORR activity will also be different. For Fe-based bimetallic-nitrogen-carbon catalysts in which the second metal is a transition metal, a large number of studies have reported that the two metals can mutually regulate the charge state of the metal atoms, thereby improving the ORR activity. For ORR catalysts in which the main group s-block metal and p-block metal couple Fe atoms, since the s / p-block metal atoms (such as Li, Na, Mg, Al, etc.) cannot provide lone pairs of electrons, the charge state of the Fe atoms is less affected, and the d orbital state of the active center of the Fe atoms can be more accurately adjusted, thereby achieving a better electron distribution in the active center to improve the catalytic activity. At the same time, the orbital interaction force between the s / p-block metal atoms and the Fe atoms is stronger, which can increase the binding strength of the Fe-N bond in the active center, thereby inhibiting the dissolution of metal ions and improving stability. At present, the method for constructing heteronuclear bimetallic catalysts is mainly to disperse the two metal sources on carbon materials (such as graphene, carbon nanotubes, etc.) or precursors (such as melamine, chitosan, etc.), and then post-treat. However, in current synthesis methods, due to the random dispersion and combination of the two metals, a variety of bimetallic or even monometallic and polymetallic configurations may exist in bimetallic-nitrogen-carbon catalysts. This hinders the acquisition of high-content heteronuclear metal atom pairs with defined relative positions and the exploration of the correlation between metal configuration and its catalytic activity. Summary of the invention
[0004] In view of this, the present application provides a heteronuclear bimetallic fuel cell oxygen reduction catalyst and its preparation method and application, which selectively dopes Li, Na, Al, etc. in the s-region and p-region, and accurately constructs bimetallic atomic sites to prepare Fe-based bimetallic-nitrogen-carbon catalysts with high intrinsic activity and high stability. The entire synthesis uses a metal organic framework (MOF) as a carrier, introduces an iron source and a metal source at the same time, and achieves precise doping through the strong adsorption between ions and MOF; the synthesis method of the present application is simple and can be quantitatively operated in equal proportions, providing a more powerful basis for the preparation of efficient heteronuclear bimetallic fuel cell oxygen reduction catalysts with precise bimetallic atomic sites, and can effectively overcome the defects of the above-mentioned prior art.
[0005] The first aspect of the present application provides a method for preparing a heteronuclear bimetallic fuel cell oxygen reduction catalyst, comprising the following steps:
[0006] S1. Dissolve the zinc source, iron source and other metal sources in an organic solvent, stir and ultrasonicate to obtain a red mixed solution;
[0007] S2, dissolving 2-methylimidazole in an organic solvent, stirring until completely dissolved, to obtain a transparent mixed solution;
[0008] S3. Slowly add the transparent mixed liquid into the red mixed liquid to react, centrifuge and collect the yellow solid after the reaction is completed, dry and grind to obtain a precursor powder, and pyrolyze the precursor powder to obtain a heteronuclear bimetallic fuel cell oxygen reduction catalyst.
[0009] Specifically, the steps include:
[0010] S1, dissolving zinc nitrate hexahydrate, anhydrous ferric chloride and a metal source in an organic solvent, stirring and ultrasonicating to obtain a red mixed solution;
[0011] S2, dissolving 2-methylimidazole in an organic solvent, stirring until completely dissolved, to obtain a transparent mixed solution;
[0012] S3. Slowly add the transparent mixed liquid into the red mixed liquid to react, centrifuge and collect the yellow solid after the reaction is completed, dry and grind to obtain a precursor powder, and pyrolyze the precursor powder to obtain a heteronuclear bimetallic fuel cell oxygen reduction catalyst.
[0013] This application achieves more accurate regulation of the electronic structure and geometric structure of the iron-based catalyst by precisely doping the main group metals in the s / p zone, achieving a balance between catalytic activity and stability, so as to promote the widespread application of Fe-based bimetallic-nitrogen-carbon catalysts in practice.
[0014] Preferably, in step S1, the other metal source is selected from one of a Li source, a Na source, and an Al source, wherein the Li source is lithium bis(oxalatoborate), the Na source is sodium difluorophosphate, and the Al source is aluminum trifluoromethanesulfonate; or
[0015] The iron source is selected from anhydrous ferric chloride, ferric nitrate, and ferric sulfate; or
[0016] The zinc source is selected from zinc nitrate hexahydrate, zinc chloride and zinc sulfate.
[0017] Preferably, in step S3, the specific conditions of the pyrolysis are: the pyrolysis temperature is 1000° C., and the pyrolysis time is 1 h.
[0018] Preferably, the usage ratio of the zinc nitrate hexahydrate, anhydrous ferric chloride, metal source and 2-methylimidazole is (0.1-1g):(0.01-0.1g):(0.01-0.1g):(1.0-5.0g).
[0019] Preferably, in steps S1 and S2, the organic solvent is methanol.
[0020] The second aspect of the present application also provides a heteronuclear bimetallic fuel cell oxygen reduction catalyst, which is a heteronuclear bimetallic fuel cell oxygen reduction catalyst prepared by the above method.
[0021] The third aspect of the present application also provides the use of the above-mentioned heteronuclear bimetallic fuel cell oxygen reduction catalyst in battery cathode materials.
[0022] The fourth aspect of the present application also provides a working electrode, which includes the above-mentioned heteronuclear bimetallic fuel cell oxygen reduction catalyst.
[0023] The fifth aspect of the present application also provides a method for preparing the above-mentioned working electrode, comprising the following steps:
[0024] 10 mg of the heteronuclear bimetallic fuel cell oxygen reduction catalyst material was weighed, and 1 mL of isopropanol was added and ultrasonicated until uniform, and then the mixture was dropped onto the disk electrode to obtain a working electrode.
[0025] Compared with the prior art, this application has the following beneficial effects:
[0026] This application will select Li, Na, Al, etc. doped in the s-region and p-region, and prepare Fe-based bimetallic-nitrogen-carbon catalysts with high intrinsic activity and high stability by accurately constructing bimetallic atomic sites. The entire synthesis uses metal organic frameworks (MOFs) as carriers, introduces iron sources and metal sources at the same time, and achieves precise doping through strong adsorption between ions and MOFs; the synthesis method of this application is simple and can be quantitatively operated in equal proportions, providing a more powerful basis for the preparation of efficient heteronuclear bimetallic fuel cell oxygen reduction catalysts with precise bimetallic atomic sites. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the technical solutions in the present application or the prior art, the drawings required for use in the description of the present application or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0028] Figure 1 This is a SEM image of the Fe / Li-NC catalyst of Example 1 of the present application;
[0029] Figure 2 This is a SEM image of the Fe / Al-NC catalyst of Example 3 of the present application;
[0030] Figure 3 It is a CV comparison chart of the Fe / Li-NC catalyst, Fe / Na-NC catalyst, Fe / Al-NC catalyst of Examples 1-3 of the present application and the Fe-NC catalyst of Comparative Example 1;
[0031] Figure 4 This is a SCV comparison chart of the Fe / Li-NC catalyst, Fe / Na-NC catalyst, Fe / Al-NC catalyst of Examples 1-3 of the present application and the Fe-NC catalyst of Comparative Example 1. DETAILED DESCRIPTION
[0032] In order to make the purpose, technical solutions and advantages of this application clearer, the technical solutions in this application will be clearly and completely described below in conjunction with the drawings in this application. Obviously, the described embodiments are part of the embodiments of this application, not all of them. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0033] Unless otherwise specified, the experimental methods used in the examples of this application are all conventional methods.
[0034] In the following examples and comparative examples, unless otherwise specified, all raw materials can be obtained by commercial purchase or conventional methods.
[0035] Example 1
[0036] 0.5g of zinc nitrate hexahydrate, 0.08g of anhydrous ferric chloride and 0.04g of lithium bis(oxalatoborate) (LiBOB) were dissolved in 50ml of methanol and stirred with ultrasound to obtain a red mixed solution. 1.5g of 2-methylimidazole was weighed and dissolved in 50ml of methanol, stirred until completely dissolved to obtain a transparent mixed solution. The transparent mixed solution was then slowly added to the red mixed solution for reaction. After centrifugation, the yellow solid was collected and placed in a forced air drying oven for drying. The dried sample was ground to obtain a Fe / Li-NC precursor powder. The Fe / Li-NC precursor powder was placed in a tubular furnace for pyrolysis at a pyrolysis temperature of 1000°C and a pyrolysis time of 1h to obtain the final Fe / Li-NC catalyst for testing.
[0037] Example 2
[0038] Except for the following steps which are different from those in Example 1, other preparation and testing methods are exactly the same as those in Example 1.
[0039] 0.5g of zinc nitrate hexahydrate, 0.08g of anhydrous ferric chloride and 0.05g of sodium difluorophosphate (NaDFP) were dissolved in 50ml of methanol and stirred with ultrasound to obtain a red mixed solution. 1.5g of 2-methylimidazole was weighed and dissolved in 50ml of methanol, stirred until completely dissolved to obtain a transparent mixed solution. The transparent mixed solution was then slowly added to the red mixed solution for reaction. After centrifugation, the yellow solid was collected and placed in a forced air drying oven for drying. The dried sample was ground to obtain Fe / Na-NC precursor powder. The Fe / Na-NC precursor powder was placed in a tubular furnace for pyrolysis at a pyrolysis temperature of 1000°C and a pyrolysis time of 1h to obtain the final Fe / Na-NC catalyst for testing.
[0040] Example 3
[0041] Except for the following steps which are different from those in Example 1, other preparation and testing methods are exactly the same as those in Example 1.
[0042] 0.5 g of zinc nitrate hexahydrate, 0.08 g of anhydrous ferric chloride and 0.09 g of aluminum trifluoromethanesulfonate (Al(TfO)3) were dissolved in 50 ml of methanol and stirred with ultrasound to obtain a red mixed solution. 1.5 gg of 2-methylimidazole was weighed and dissolved in 50 ml of methanol, stirred until completely dissolved to obtain a transparent mixed solution. The transparent mixed solution was then slowly added to the red mixed solution for reaction. After centrifugation, the yellow solid was collected and placed in a forced air drying oven for drying. The dried sample was ground to obtain a Fe / Al-NC precursor powder. The Fe / Al-NC precursor powder was placed in a tubular furnace for pyrolysis at a pyrolysis temperature of 1000°C and a pyrolysis time of 1 h to obtain the final Fe / Al-NC catalyst for testing.
[0043] Comparative Example 1
[0044] The preparation method provided in this comparative example can refer to Example 1, except that no other metal sources are introduced to obtain the final Fe-NC catalyst for testing.
[0045] Test Case
[0046] 10 mg of each of the electrocatalyst materials in Examples 1-3 and the electrocatalyst material in Comparative Example 1 were weighed, and 1 mL of isopropanol was added successively and ultrasonicated until uniform. After uniformity, the mixture was dropped onto a disk electrode to test the oxygen reduction electrochemical performance. Figure 1 It can be seen that the prepared Fe / Li-NC catalyst did not change the original octahedral structure of ZIF-8 after the introduction of the second metal lithium source, the size was uneven, and no obvious metal nanoparticles were produced.
[0047] Figure 2 It can be seen that the prepared Fe / Al-NC catalyst did not change the original octahedral structure of ZIF-8 after the introduction of the second metal aluminum source. The size was relatively uniform and no obvious metal nanoparticles were produced.
[0048] Figure 3 It can be seen that the heteronuclear bimetallic catalysts prepared by introducing a second different metal source have different electrochemical activities. Through the comparison of the electrochemical active areas, it can be seen that the Fe / Li-NC catalyst has the best oxygen reduction activity, followed by the Fe / Na-NC catalyst, then the Fe / Al-NC catalyst, and finally the Fe-NC catalyst.
[0049] Figure 4 It can be seen that the heteronuclear bimetallic catalysts prepared by introducing a second different metal source have different oxygen reduction performance. In the acidic electrolyte test, the half-wave potential (E 1 / 2) can reach 0.82V, while the E of Fe / Al-NC catalyst, Fe / Na-NC catalyst, and Fe-NC catalyst 1 / 2 They are 0.80V, 0.79V, and 0.78V respectively.
[0050] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
Claims
1. A method for preparing a heteronuclear bimetallic fuel cell oxygen reduction catalyst, characterized in that: The following steps are involved: S1. Dissolve the zinc source, iron source and other metal sources in an organic solvent, stir and ultrasonicate to obtain a red mixed solution; S2, dissolving 2-methylimidazole in an organic solvent, stirring until completely dissolved, to obtain a transparent mixed solution; S3. Slowly add the transparent mixed liquid into the red mixed liquid to react, centrifuge and collect the yellow solid after the reaction is completed, dry and grind to obtain a precursor powder, and pyrolyze the precursor powder to obtain a heteronuclear bimetallic fuel cell oxygen reduction catalyst.
2. The method for preparing a heteronuclear bimetallic fuel cell oxygen reduction catalyst according to claim 1, characterized in that: In step S1, the other metal source is selected from one of a Li source, a Na source, and an Al source, wherein the Li source is lithium bis(oxalatoborate), the Na source is sodium difluorophosphate, and the Al source is aluminum trifluoromethanesulfonate; or The iron source is selected from anhydrous ferric chloride, ferric nitrate, and ferric sulfate; or The zinc source is selected from zinc nitrate hexahydrate, zinc chloride and zinc sulfate.
3. The method for preparing a heteronuclear bimetallic fuel cell oxygen reduction catalyst according to claim 1, characterized in that: In step S3, the specific conditions of the pyrolysis are: the pyrolysis temperature is 1000° C. and the pyrolysis time is 1 hour.
4. The method for preparing a heteronuclear bimetallic fuel cell oxygen reduction catalyst according to claim 1, characterized in that: The usage ratio of the zinc nitrate hexahydrate, anhydrous ferric chloride, metal source and 2-methylimidazole is (0.1-1g):(0.01-0.1g):(0.01-0.1g):(1.0-5.0g).
5. The method for preparing a heteronuclear bimetallic fuel cell oxygen reduction catalyst according to claim 1, characterized in that: In steps S1 and S2, the organic solvent is methanol.
6. A heteronuclear bimetallic fuel cell oxygen reduction catalyst, characterized in that: A heteronuclear bimetallic fuel cell oxygen reduction catalyst prepared by the method described in any one of claims 1 to 5.
7. Use of the heteronuclear bimetallic fuel cell oxygen reduction catalyst according to claim 6 in battery cathode materials.
8. A working electrode, characterized in that It comprises the heteronuclear bimetallic fuel cell oxygen reduction catalyst as claimed in claim 6.
9. A method for preparing the working electrode according to claim 8, characterized in that: The following steps are involved: 10 mg of the heteronuclear bimetallic fuel cell oxygen reduction catalyst material was weighed, and 1 mL of isopropanol was added and ultrasonicated until uniform, and then the mixture was dropped onto the disk electrode to obtain a working electrode.
Citation Information
Patent Citations
Iron, cobalt and nitrogen codoped carbon catalyst and preparation method and application thereof
CN107086313A
High-activity Co-Ni-Fe co-inlaid non-noble metal catalyst as well as preparation method and application thereof
CN112691688A
Fe-N-C CATALYST, METHOD OF PREPARATION AND USES THEREOF
WO2019158516A1